The Development of Innovative Dosage Forms of the Fixed-Dose Combination of Active Pharmaceutical Ingredients - Magdalena Janczura; Szymon Sip; Judyta Cielecka-Piontek (MDPI AG, 2022)
The development of innovative forms of combination drugs is closely related to the invention of the multilayer tablet press, polymers for pharmaceutical applications, the hot-melt extrusion process, and 3D printing in the pharmaceutical industry. However, combining multiple drugs within the same dosage form can bring many physicochemical and pharmacodynamic interactions. More and more new forms of fixed-dose combinations (FDCs) have been developed due to work to overcome the incompatibility of active substances or to obtain different drug release profiles in the same dosage form. This review provides discussions of the application of various innovation formulation technologies of FDC drugs such as bilayer system, multilayer tablet, active film coating, hot-melt extrusion, and 3D printing, taking into account the characteristics of the key ingredients in the FDC formulation and presenting technological problems and challenges related to the development of combination drugs. Moreover, the article summarizes the range of dosage forms that have been made using these technologies over the past 30 years.